The first published of folk songs of Chinese Tuvinians - Yusha, Zhanna M. (The New Research of Tuva, 2017)
This is a review of a book: Kydat tyvalarnyң chon yry. 中国 图瓦 歌曲. Khatad dakh' tuvachuudyn ardyn duu (Pesni kitaiskikh tuvintsev) [Songs of Chinese Tuvans] (2016), comp. Taivan Chaa. Ürümqi (乌鲁木齐). 290 p. (In Tuv., Mong., Chinese)Put together by Taivan Chaa and published in three languages in the capital of Xingjiang Uyghur Autonomous Region, this book is the first collection of song folklore of Chinese Tuvans which appears in an accessible edition.The review focuses on the book’s structure, song distribution by thematic segments, and the detailed transcripts of the song lyrics. We believe these helped outline both the dialectal features of the language spoken by Tuvans in China and the compositional peculiarities of their lyrics. An important achievement is also the publication of versions of the same songs recorded in the various areas with Tuvan population.
Keywords: Chinese Tuvans; folklore; folk songs; musical folklore; sub-ethnic groups of Tuvans; review